Aggravated cognitive impairment in maintenance hemodialysis patients——3 cases report - GAO Zhi-chao; CHEN Yu-qing (Linchuang shenzangbing zazhi)
Objective To report three cases of aggravated cognitive impairment during hemodialysis and to explore the potential causes and treatments. Methods There were 3 patients,include 2 males and 1 female,developed cognitive impairment during dialysis. They all aged 72 ~ 82 years with dialysis duration of1 ~ 14 years. And other 44 patients with age over 70 years without cognitive dysfunction served as control group include 21 males and 23 females,mean age(76. 6 + 5. 1) years old,the average duration of dialysis(86. 3 + 68. 2) months. Dialysis prescriptions,parameters,and biochemical results of the three patients and the control group were collected. We then compared the characteristics of the 3 patients at stable stage,symptomatic stage and stage after treatment. We also compared the 3 cases with the control group. Results There was no significant difference between the 3 cases and control group in dialysis time,blood flow velocity,URR,spKT/V,serum sodium concentration and osmotic pressure before and after dialysis( P > 0. 05).Conclusions The occurrence of cognitive dysfunction during dialysis in the 3 cases may be associated with decreased tolerance to the osmotic pressure change,elder age,essential brain injury,and complications.The symptoms can be alleviated by a mild dialysis prescription.